Thermospheric Neutral Winds as the Cause of Drift Shell Distortion in Earth’s Inner Radiation Belt - Lejosne, Solène; Fedrizzi, Mariangel; Maruyama, Naomi; Selesnick, Richard S. (Frontiers in Astronomy and Space Sciences, 2021)
Recent analysis of energetic electron measurements from the Magnetic Electron Ion Spectrometer instruments onboard the Van Allen Probes showed a local time variation of the equatorial electron intensity in the Earth’s inner radiation belt. The local time asymmetry was interpreted as evidence of drift shell distortion by a large-scale electric field. It was also demonstrated that the inclusion of a simple dawn-to-dusk electric field model improved the agreement between observations and theoretical expectations. Yet, exactly what drives this electric field was left unexplained. We combine in-situ field and particle observations, together with a physics-based coupled model, the Rice Convection Model (RCM) Coupled Thermosphere-Ionosphere-Plasmasphere-electrodynamics (CTIPe), to revisit the local time asymmetry of the equatorial electron intensity observed in the innermost radiation belt. The study is based on the dawn-dusk difference in equatorial electron intensity measured at L=1.30 during the first 60 days of the year 2014. Analysis of measured equatorial electron intensity in the 150-400 keV energy range, in-situ DC electric field measurements and wind dynamo modeling outputs provide consistent estimates of the order of 6 to 8 kV for the average dawn-to-dusk electric potential variation. This suggests that the dynamo electric fields produced by tidal motion of upper atmospheric winds flowing across Earth’s magnetic field lines - the quiet time ionospheric wind dynamo - are the main drivers of the drift shell distortion in the Earth’s inner radiation belt.